Global, regional, and national burden of atrial fibrillation/flutter attributable to metabolic, behavioral, and environmental risk factors, 1990–2021: a longitudinal observational study - Wei, Zhen; Wang, Qi; Jia, Hong-Ling (Frontiers in Nutrition, 2025)
BackgroundAtrial fibrillation/flutter (AF/AFL) remains a significant global public health issue, with its development influenced by metabolic, behavioral, and environmental risk factors However, comprehensive analyses of temporal and geographic variations in AF/AFL burden attributed to risk factors remain lacking.ObjectiveThis study reveals the geographic and temporal distribution of the burden of AF/AFL attributable to specific risk factors at global, regional, and national levels from 1990 to 2021, providing a scientific basis for developing targeted prevention and control policies.MethodsWe extracted data on AF/AFL risk-attributable deaths, disability-adjusted life years (DALYs), age-standardized mortality rates (ASMRs), and age-standardized DALY rates (ASDRs) from the Global Burden of Disease (GBD) database for the years 1990 to 2021. The burden of AF/AFL caused by metabolic, behavioral, and environmental risk factors stratified by age, sex, region, and country. Long-term trends in the AF/AFL burden associated with specific risk factors were assessed using the average annual percentage change (AAPC).ResultsOver the past 32 years, high body mass index has been the primary contributor to the rising AF/AFL burden, with AAPCs of ASMR and ASDR at 1.66 (95% CI: 1.63–1.68) and 1.68 (95% CI: 1.67–1.70), respectively. The most significant increase occurred in males aged 30–34. The burden related to high sodium diets and lead exposure is also rising, particularly in females aged 65–69. Smoking showed the greatest decrease, with AAPCs of ASMR and ASDR at −0.66 (95% CI: −0.68 to −0.65) and −0.72 (95% CI: −0.72 to −0.71), most significantly in women aged 30–34. High systolic blood pressure decreased overall, but increased in individuals aged 34–49. East Asia saw the largest increase in burden from high body mass index, with AAPCs of ASMR at 8.28 (95% CI: 8.18–8.37) and ASDR at 8.22 (95% CI: 8.18–8.26). In 2021, China had the highest AF/AFL deaths and DALYs attributed to high systolic blood pressure, high sodium diets, smoking, and lead exposure.ConclusionFrom 1990 to 2021, high body mass index became the primary driver of the rising global AF/AFL burden, particularly affecting East Asia and young and middle-aged adults. In contrast, the burden associated with smoking showed the greatest decline. In 2021, China had the highest AF/AFL burden due to various risk factors. Given the regional variations and characteristics of high-risk populations, policymakers should develop targeted yet comprehensive prevention strategies. These measures should include promoting healthy dietary habits, strengthening global surveillance systems, and fostering data-sharing collaborations to mitigate this growing epidemic.